2021
DOI: 10.21809/rilemtechlett.2021.130
|View full text |Cite
|
Sign up to set email alerts
|

Rehydration of katoite as a layered double hydroxide: an in situ study

Abstract: Calcium aluminate layered double hydroxides (Ca-Al LDHs) constitute a considerable part of cementitious waste fines. Although cementitious waste fines have proven to be recyclable by thermal treatment at moderate temperatures (400–700 °C), understanding how each phase rehydrates and contributes to the binding properties of rehydrated cementitious materials is still necessary. In this study, the de(re)hydration of katoite is investigated through in situ techniques, and its applicability as an alternative cement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…This was consistent with the rapid development of binding properties during monocarboaluminate (CaAl-LDH) formation from the rehydration of calcined katoite Ca 3 Al 2 (OH) 12. Furthermore, the recovered LDH could also induce the heterogeneous nucleation of the system (cement/water) to form hydrated products, especially the aluminate layered double hydroxides …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was consistent with the rapid development of binding properties during monocarboaluminate (CaAl-LDH) formation from the rehydration of calcined katoite Ca 3 Al 2 (OH) 12. Furthermore, the recovered LDH could also induce the heterogeneous nucleation of the system (cement/water) to form hydrated products, especially the aluminate layered double hydroxides …”
Section: Resultsmentioning
confidence: 99%
“…This was consistent with the rapid development of binding properties during monocarboaluminate (CaAl-LDH) formation from the rehydration of calcined katoite Ca 3 Al 2 (OH) 12. 61 Furthermore, the recovered LDH could also induce the heterogeneous nucleation of the system (cement/water) to form hydrated products, especially the aluminate layered double hydroxides. 5 The rheological behavior observed during LDH regeneration in simulated concrete pore solution (Figure S7) demonstrated that in the initial minutes of the test, the storage component was greater than G′ of the reference cement paste, with the value increasing further as the lamellae reconstruction continued, because of crystallite aggregative growth in the c direction.…”
Section: Pfmentioning
confidence: 99%
“…When anhydrous calcined fines are exposed to water again, they rapidly regain chemically bound water (XINWEI;ZHAOXIANG;XUEYING, 2010;ANGULO et al, 2015a;LIMA PACHECO et al, 2021). The R-PC generates a large amount of heat in the first few minutes of rehydration as ordinary Portland cement (OPC) (ANGULO et al, 2015a), recovering combined water in C-S-H (ANGULO et al, 2022), in part of the CaO (quicklime) formed (MENÉNDEZ;ANDRADE;VEGA, 2012).…”
Section: Introductionmentioning
confidence: 99%